Analysis of Cyanide (CN) Compounds in Gewang Fruit (Corypha utan Lamk) - Vedy Yeriel Koy; James Ngginak; Novi Ivone Bullu (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2025)
Plants in general are able to produce secondary metabolite compounds that act as a protector against predators. Gewang fruit is often used by the people of Kolbano Village as a natural poison to catch fish.. The purpose of this study is to analyze the cyanide (CN) compound content in gewang fruit (Corypha utan Lamk). This study uses a trimetric method. There are two types of samples used in this study, namely raw samples and dry samples. The results of the qualitative testing of the cyanide compound content in the gewang fruit on 2 (two) samples showed that the color changed from yellow to white and a precipitate was formed at the bottom of the solution when reacted with AgNO₃, which showed that the gewang fruit positively contained cyanide compounds (CN). The average cyanide content in the raw gewang fruit samples was 11.52 mg/L or 9.25%. Meanwhile, the average cyanide level in the dry samples was 18 mg/L or 17,19 %.